2019
DOI: 10.1016/j.pt.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

100 Questions in Livestock Helminthology Research

Abstract: An elicitation exercise was conducted to collect and identify pressing questions concerning the study of helminths in livestock, to help guide research priorities. Questions were invited from the research community in an inclusive way. Of 385 questions submitted, 100 were chosen by online vote, with priority given to open questions in important areas that are specific enough to permit investigation within a focused project or programme of research. The final list of questions was divided into ten themes. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 99 publications
0
54
0
2
Order By: Relevance
“…In fact, Precision Livestock Farming (i.e., the application of process engineering principles and techniques to livestock farming to automatically monitor, model and manage animal production) is now a reality in different settings (36,37). Based on this strategy, it is fundamental to promote also a "Precision Parasitology, " using best practices of diagnosis and control of livestock helminths also to reduce the environmental impact of livestock farming, which is one of the main goals of the Precision Livestock Farming concept (38,39).…”
Section: Social Factorsmentioning
confidence: 99%
“…In fact, Precision Livestock Farming (i.e., the application of process engineering principles and techniques to livestock farming to automatically monitor, model and manage animal production) is now a reality in different settings (36,37). Based on this strategy, it is fundamental to promote also a "Precision Parasitology, " using best practices of diagnosis and control of livestock helminths also to reduce the environmental impact of livestock farming, which is one of the main goals of the Precision Livestock Farming concept (38,39).…”
Section: Social Factorsmentioning
confidence: 99%
“…This is a prerequisite for the planning and implementation of interventions (4). Questionnaire surveys of ruminant gastrointestinal nematode management practices have helped to inform our understanding the factors that influence farmers' behaviors in different specific regions (2,(5)(6)(7)(8). This insight is necessary in order to optimize communication strategies and to improve compliance with specialist advice.…”
Section: Introductionmentioning
confidence: 99%
“…This insight is necessary in order to optimize communication strategies and to improve compliance with specialist advice. However, the factors that drive farmers' decisions concerning sustainable helminth management will differ according to the society to which they belong (8).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, helminth transmission models can be a useful tool for evaluating different scenarios in silico, and to select the most promising (combinations of) control methods for field testing. 41,42 Barnes and colleagues 43 modeled the population dynamics of Trichostrongylus colubriformis in sheep to predict the effect of different vaccines on worm population dynamics in grazing lambs. They concluded that, with vaccines based on conventional antigens, substantial benefits can be obtained with a decrease of 60% in larval establishment in 80% of the flock.…”
Section: Vaccination and Other Worm Control Measuresmentioning
confidence: 99%
“…2 The sustainability of vaccines, like anthelmintics, will depend on parasite evolution, and the ability of helminths to develop resistance to vaccine-induced host responses remains an open question. 41 Vaccines containing multiple antigens of a single parasite species could slow down adaptation of the parasites to the vaccine, such as an experimental Teladorsagia vaccine in sheep that comprises multiple recombinant proteins. 14,16 The effect of the level and duration of vaccine efficacy on parasite transmission and animal productivity and the combined use of vaccines and other control methods in different management systems and climate regions should be simulated using mathematical models to inform vaccine developers and regulatory authorities about possible outcome scenarios.…”
Section: Future Prospects and Summarymentioning
confidence: 99%